1990
DOI: 10.1111/j.1365-2621.1990.tb06755.x
|View full text |Cite
|
Sign up to set email alerts
|

Textural and Chemical Characteristics of Recombined Precooked Beef Chuck Roasts as Influenced by Boning Time and Salt Level

Abstract: The effects of hot-boning (HB) and salt level (SL) (0, 0.5, 1.0%) on recombined precooked roasts from three beef chuck recombined whole muscles were investigated using a system that employed electrical stimulation, blade tenderization, vacuum massage and the addition of phosphate. SL and muscle type (MT) significantly affected proximate composition (protein, fat and moisture). Maximum yields were obtained with hot-boned treatments at the highest salt level. Instron measurements were affected by MT, HB and SL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Knight (1992) reported that the addition of salt and phosphate enhanced the hardness due to the increased ionic strength and Claus et al (1989) reported that an increase in the amount of salt soluble proteins tended to increase the hardness of the meat products. Similar results were reported by Claus and Sørheim (2006) and Mann et al (1990). Knight (1992) reported that when the salt concentration in ground meat products was increased, the hardness increased and the structure changed substantially with the increased ionic strength.…”
supporting
confidence: 78%
“…Knight (1992) reported that the addition of salt and phosphate enhanced the hardness due to the increased ionic strength and Claus et al (1989) reported that an increase in the amount of salt soluble proteins tended to increase the hardness of the meat products. Similar results were reported by Claus and Sørheim (2006) and Mann et al (1990). Knight (1992) reported that when the salt concentration in ground meat products was increased, the hardness increased and the structure changed substantially with the increased ionic strength.…”
supporting
confidence: 78%
“…The higher salt concentration increased the water binding capacity of the meat which caused a subsequent dilution of the protein content, although the fat content was not statistically different. Numerous researchers have reported the effect of salt level on water binding properties with a variety of meat products (Hamm, 1970;Mann, 1987;Shackelford et al, 1989). Fat level of the precooked roasts was affected by grinding method (GM), as those roasts ground through the kidney plate only contained less fat (P < 0.05) than roasts that contained the additional coarse ground trimmings.…”
Section: Proximatementioning
confidence: 99%
“…Recent work involving the restructuring of beef chuck muscles into precooked roasts has shown that certain processing parameters such as added salt, vacuum massage and blade tenderization are needed in order to achieve a final product that retains its bind, while remaining within an acceptable range of tenderness (Mann, 1987: Shackelford et al, 1989. The techniques used by these workers to recombine beef chuck muscles into a desirable, precooked roast product should be applicable to lamb shoulder muscles as well, as lamb muscle shows the same general biochemical and physical responses as other meats (Carse, 1973;Bendall, 1976;Chrystall and Hagyard, 1976;Bowling et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…RESTRUCTURING TECHNOLOGY makes it possible to produce value-added meat products from low quality cuts. A wide variety of raw materials such as chuck muscles (Recio et al, 1987;Mann et al, 1990) beef riblifter (Ensor et al, 1990), shoulder clods (Liu et al, 1990) lamb (Field et al, 1984) mutton (Prasad et al, 1987), pork (Huffman et al, 1987;Trout et al, 1990) turkey Ensor et al, 1989) and chicken (Xiong and Brekke,199 1) have been used to produce restructured products. Traditionally, salt and phosphate have been used in restructured meat products because of beneficial effects on cohesion, cook yield, juiciness, and flavor Mann et al, 1989;Wheeler et al, 1990, Craig et al, 1991Liu et al, 1992).…”
Section: Introductionmentioning
confidence: 99%